Effects of Ddc cluster lethal alleles on ovary growth, attachment, and egg production in Drosophila. - McCrady, E.; Tolin, D.J. (Journal of Experimental Zoology, 1994)
The Ddc cluster of genes on the left arm of chromosome 2 in Drosophila has been extensively characterized by Wright and coworkers (Wright, '87b). Many of the genes in the cluster are associated with the pigmentation and sclerotization of the cuticle, and at least 12 have been shown to play a role in female fertility. To characterize further the actions of genes in the cluster, we have investigated the effect on fertility of a total of five of the previously untested genes (l(2)37Be, Bb, Bg, Bd, and Cg), and three of the partially characterized genes (l(2)37Ce, Ddc, and amd). Each allele was crossed to Df(2L)TW130 or49h flies in order to make it hemizygous over the 8-12 band deficiency covering the Ddc region, 37B9-C1,2;37D1-2. Ovaries taken from larvae produced by this cross were transplanted into female larval hosts of y f mal genotype, that were then mated to v f mal males. The wild type allele of mal in implanted tissue allowed identification and study of surviving implants by staining for the presence of aldehyde oxidase. Of the 18 alleles available, amdH149, l(2)37Bb1, Bb9, Bb11, Bd6, Be1, Bd7, Be2, Be3, Ce4, and Cg1 did not allow enough growth to form transplantable ovaries; l(2)37Bg1, Bg2, and Cgts1 prevented development of transplanted ovaries in their hosts; l(2)37Ce5 allowed implanted ovaries to attach to oviducts and grow, but insufficiently for production of eggs; and DdcN27, amd29, and l(2)37Bd4 appeared not to restrict ovary development. Heteroallelic heterozygotes of Bd7 x Bd4 also produced fully fertile ovaries, but no other heteroallelic combinations did so.(ABSTRACT TRUNCATED AT 250 WORDS)